Magnetic micro/nanoparticle flocculation-based signal amplification for biosensing - Mzava O (Dove Medical Press, 2016)
Omary Mzava,1 Zehra Tas,1 Kutay İçöz1,2 1BioMINDS (Bio Micro/Nano Devices and Sensors) Laboratory, Department of Electrical and Electronics Engineering, 2Bioengineering Department, Abdullah Gül University, Kayseri, Turkey Abstract: We report a time and cost efficient signal amplification method for biosensors employing magnetic particles. In this method, magnetic particles in an applied external magnetic field form magnetic dipoles, interact with each other, and accumulate along the magnetic field lines. This magnetic interaction does not need any biomolecular coating for binding and can be controlled with the strength of the applied magnetic field. The accumulation can be used to amplify the corresponding pixel area that is obtained from an image of a single magnetic particle. An application of the method to the Escherichia coli 0157:H7 bacteria samples is demonstrated in order to show the potential of the approach. A minimum of threefold to a maximum of 60-fold amplification is reached from a single bacteria cell under a magnetic field of 20 mT. Keywords: magnetic micro/nanoparticle accumulation, signal amplification, image-based detection, magnetic dipole–dipole interaction